Outcomes of Sacrococcygeal Teratoma: An 18-year Experience in a Single Tertiary Referral Center in Thailand - Suksamanapun N. (2023)
Introduction: Pediatric sacrococcygeal teratoma (SCT), yet a rare tumor, is a common solid tumor among neonates. Although overall survival is excellent, tumor recurrence may compromise the outcomes. Objectives: The aim of this study is to determine overall survival rate, tumor recurrence rate, and associated factors for recurrence. Materials and Methods: A retrospective chart review of patients admitted to Siriraj Hospital with SCT (2000-2018) was performed. Data were collected and analyzed for the association with outcomes, including survival rate, and tumor recurrence. Results: Forty-one patients were included. Overall survival was 95.1%. Two patients died, one due to bleeding from perinatal tumors rupture and the other due to post-chemotherapy complications. Twenty-three patients who achieved at least 3-year period of follow-up. Among those, 2 patients developed recurrences which were significantly associated with late presentation, small tumor size, potentially malignant histology, and Altman type IV. Overall bowel or bladder dysfunctions were found in 8 patients. Conclusion: Overall survival in SCTs was excellence. Recurrence occurred at 8.6%. However, it did not negatively influence the survival rate. Early diagnosis and complete tumor removal including the coccyx are crucial for minimizing tumor recurrence. Long-term follow-up and prompt intervention might improve outcomes of recurrent disease.